1996
DOI: 10.1097/00004872-199605000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic neutrality of combined verapamil-trandolapril treatment in contrast to beta-blocker-low-dose chlortalidone treatment in hypertensive type 2 diabetes

Abstract: Objective To investigate the metabolic, antihypertensive and albuminuria-modifying effects of a heart rate-modulating calcium antagonist-angiotensin converting enzyme inhibitor combination compared with those of a p-blockerlow-dose diuretic combination in non-insulin-dependent diabetic hypertensives.Design A prospective randomized double-blind study. Subjects and methodsTwenty-four diabetics with diastolic blood pressure 90-115 mm Hg without azotemia (plasma creatinine level < 150jimol/l) were evaluated after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The combination verapamil SR and trandolapril has been shown to be metabolically neutral 26 compared to atenolol/chlorthalidone in hypertensive type 2 diabetic patients. The latter combination induced a marked increase in triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…The combination verapamil SR and trandolapril has been shown to be metabolically neutral 26 compared to atenolol/chlorthalidone in hypertensive type 2 diabetic patients. The latter combination induced a marked increase in triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…59 The combination of ␤ -blocker with a thiazide can lead to an increase in plasma glucose levels and should be used with caution. 60,61 Lipids Characteristically, persons with type II diabetes have elevated triglyceride and very-low-density lipoprotein (VLDL) levels, while HDL levels are low. Low-density lipoprotein levels can also be elevated.…”
Section: Hypertensionmentioning
confidence: 99%
“…Trandolapril was shown to enhance skeletal muscle insulin action and GLUT-4 protein levels in insulin resistant obese rats and it had no effect in insulin sensitive lean rat muscle [19]. In contrast to experimental studies most of the clinical studies conducted indicated that trandolapril has a neutral effect on IR [13][14][15]20]. Only in one clinical study conducted in overweight hypertensive patients with low grade IR trandolapril improved insulin sensitivity moderately compared to nifedipine in the absence of severely obese and diabetic individuals [21].…”
Section: Discussionmentioning
confidence: 98%
“…Although it was shown to improve IR in insulin resistant obese Zucker or spontaneously hypertensive rat studies [11,12], many clinical studies showed that trandolapril has a neutral effect on IR in hypertensive patients with type 2 DM [13][14][15]. As trandolapril is a lipophylic agent [10], by acting on adipose tissue, it might be more efficient in obese subjects by tissue ACE inhibition.…”
Section: Introductionmentioning
confidence: 99%